List of voyages and station parties between 1947 and 1989 in which Australians participated, including winter and some summer personnel - BARRETT (DECEASED), EVLYN (hasPrincipalInvestigator); Australian Antarctic Data Centre (publisher)
This document contains detailed descriptions of Antarctic and subantarctic voyages undertaken by Australians or in which Australians participated in between 1947 and 1989. It also includes lists of wintering personnel at Heard Island, Macquarie Island, Mawson, Casey, Davis, Wilkes and various field parties. Some information about summer personnel has also been recorded. The voyages are presented in chronological order, and contain information such as the name of the ship, dates of the voyage, destination, ship's master, and personnel details. The document also contains some details of Antarctic and subantarctic flights undertaken in support of the voyages (e.g. by the RAAF - Royal Australian Air Force). A second file (a spreadsheet) provides the number of personnel wintering at ANARE (Australian National Antarctic Research Expeditions) stations between 1948 and 1982. These stations include Heard Island, Macquarie Island, Davis, Wilkes, Repstat (Replacement Station at Wilkes), Casey and the Amery Ice Shelf.